Differentiation of Innovative Development Strategies Considering Specific Characteristics of the Russian Regions - Irina Markovna Golova; Alla Filippovna Sukhovey (Экономика региона, 2019)
We consider differentiation of innovative development strategy as a condition for successful regional development. The relevance of the differentiation of regional innovation strategies is determined by inefficiency of the current strategies. This inefficiency manifest s itself in the unificati on of region al policies, isolation of innovative development from the territories’ socio-economic potential, deformation of mechanism regulating industrial proportions of the country’s economy, in particular, imbalances in favour of supporting resource-based industries. The study aims to develop methodological approaches to the establishment of effective innovative strategies for different types of regions considering their relevant socio-economic needs and existing scientific, technological, productive and human capacities. Based on the analysis of Russian and international experience, we have proven that such factors as region’s research and production specialisation, its position in the “centreperiphery” system, and the existence and the structure of demand for innovation greatly influence the success of innovative strategies. Due to a high differentiation of the Russian regions for production specialisation, we paid special attention to the impact of the territory’s production and technology type on the choice of optimal paths for establishing an innovation system. We identified and substantiated the main elements of the innovative strategy in relation to the Russian regions with a large concentration of high-tech industries (mission, key elements of the innovative system, priority areas of the State support, expected results). We have formulated the specific characteristics of the author’s method of selecting priorities for region’s innovative development. It is based on the assessment and comparison of the development levels of scientific, technological and innovative capacities of the Russian regions and their production and technology type, taking into account the spatial differentiation of various types of industries. The article is addressed to professionals in the sphere of the theory and practice of managing region’s innovative development.